Electric-driven windows for historical buildings retrofit: Energy and visual sensitivity analysis for different control logics. (September 2020) - Scorpio, Michelangelo; Ciampi, Giovanni; Rosato, Antonio; Maffei, Luigi; Masullo, Massimiliano; Almeida, Manuela; Sibilio, Sergio
Abstract: This paper uses the dynamic simulation software Transient System Simulation Tool to analyze the benefits of using dynamic electrical-driven glazing to refurbish the windows of historical buildings from an energy, environmental and visual points of view. For the visual analysis, Transient System Simulation Tool and Radiance were coupled. A south oriented office within the Abbey of San Lorenzo ad Septimum, located in Aversa (southern Italy), was considered for the simulations. The simulations were performed considering five window control strategies, two liquid crystal based electrical-driven glazing (able to switch faster than 1 s from an opaque to a transparent state) and two simulation switching times (1 h and 15 min). The simulation results associated with the electric-driven windows were compared to those obtained for a conventional double Low-E glazing window, highlighting that: (i) the use of the examined dynamic glazing can help to improve both the energy efficiency as well as the internal visual comfort, (ii) the effects of the control strategy are strongly related to the thermal and visual characteristics of the dynamic window and (iii) by reducing the switching time of the window, it is possible to improve the energy saving as well as the comfort inside the office. Highlights: The feasibility of the window refurbishment using active smart glazing is analyzed. The window refurbishment associated with a typical historical building is assessed. The impact of the control strategy on the smart window performances is assessed. The results are compared with those related to a conventional double-glazing window. The comparison is performed form energy, environmental and visual points of view.